Adjudicating fake news - Filippo Maria Lancieri; Caio Mário da Silva Pereira Neto; Rodrigo Moura Karolczak; Barbara Marchiori De Assis (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
On July 30, 2025, President Trump imposed 50% tariffs on imports from Brazil and sanctioned a sitting Brazilian Supreme Court Justice, both partially because of Brazil's online content moderation decisions. This is an extreme, but not an isolated event: worldwide, legislators and regulators struggle to craft public policies that address problems of disinformation and online harassment while protecting the freedom of expression - leading to increasing international confrontations. One key question in content moderation is content adjudication - or who is responsible for deciding what type of speech violates the law and should be taken down. This article presents the results of a six-year, large empirical and qualitative project on the adjudication of fake news disputes by Brazilian Courts from 2018 onwards. It examines what led Brazilian judges to order the takedown of online content, which social networks and types of content were most affected by judicial decisions, and whether there is evidence that incumbent politicians abused the system, among other factors. It also critically analyzes the evolution of this novel courtdriven content moderation regime - one in which Courts play an increasingly active role in policing online discourse - with significant implications for the Brazilian information ecosystem, democratic institutions, and judicial reputation. Ultimately, the Brazilian experience teaches/reinforces five lessons to jurisdictions rethinking their online content moderation regulatory regimes: (i) content moderation systems must articulate clear end goals to work properly; (ii) experimentation in content moderation regulation is possible and desirable, allowing for incremental learning and adaptation; (iii) a content moderation system must have strict protection against the slippery slope that may lead it to censorship and arbitrariness; (iv) contentbased moderation systems become part of the information environment - claims about neutrality in adjudication cannot, by themselves, support long-term systemic legitimacy; (v) increasing regulatory fragmentation impose new urgency on the development of international guidelines for limits on the extraterritoriality of online decisions.
Keywords: 330